SINGLE-DOSE ORAL TOXICITY AND ACUTE DERMAL IRRITATION OF STEAMED AND DRIED GINGER EXTRACT IN RAT AND WHITE RABBIT - Jae Young Kim; Jae-Suk Choi (Journal of Animal and Plant Sciences, 2017)
The objective of this study was to determine the acute oral toxicity of steamed and dried ginger (Zingiber officinale Roscoe, Zingiberaceae) extract (SDGE) in female and male Sprague-Dawley (SD) rats at doses of 0 and 5,000 mg/kg body weight. After a single oral dose of SDGE, no treatment-related mortalities were observed within 14 days of treatment up to 5,000 mg/kg, which is 2.5 times the limited dosage for rodents of both sexes. No SDGE-related changes in body weight, clinical signs, or necropsy and histopathological findings were detected. The results suggest that SDGE is non-toxic in rats. To determine the potential utility of SDGE in dermal applications, we investigated the acute dermal irritation potential of SDGE in New Zealand white rabbits. No abnormal clinical signs attributable to SDGE were detected. In the dermal irritation test, erythema, eschar, and edema formation were observed after 24 h of treatment, but the skin returned to normal after 72 h. SDGE had a dermal primary irritation index of 0.0, showing that it was a non-irritant. These results indicate that SDGE is non-toxic to the body and non-irritating to the skin, suggesting that it can be used in pharmaceutical and dermal applications with no serious toxic effects at moderate doses.
Keywords: Acute oral toxicity; dermal irritation test; steamed and dried ginger extract (SDGE); Zingiber officinale